Newborns from assisted reproductive technology at the Hospital de São João. - Teixeira, Ana (2005)
Over the last 20 years, assisted reproductive technology has been increasingly used. Ever since the first newborn resulting from artificial insemination, over two centuries ago, thousands more children were born resulting from these techniques. In Portugal, assisted reproductive technology began in 1985 at the Hospital de São João (HSJ). Although the success of these techniques is often judge by the pregnancy rate, occasionally by the birth rate, the most important issue of this evaluation should be the neonatal health. A retrospective study to evaluate the use of assisted reproductive technology at the HSJ, as well as the occurrence of complications during pregnancy and the evolution of the newborns in the neonatal period, during the period between 1999 and 2003, was undertaken. A hundred and thirty-eight pregnant women were included, which stands for about 1% of the total number of pregnant women at the HSJ in the period in question, with an average of age 32.2 +/- 4.1 and of infertility 6.2 +/- 3.8 years. The number of attempts for a successful pregnancy was 2.7 +/- 2.1. The most used technique was intracytoplasmatic sperm injection. Eighteen percent of the pregnancies resulted in abortion. The incidence of multiple pregnancies was 30%. A hundred and fifty-six infants were born, which stands for about 1% of the total number of births at the HSJ in the period in question, with a gestational age of 36.4 +/- 3 weeks and weight at birth of 2674.5 +/- 761.4 g. The incidence of preterm birth was 41%. Seventy-eight percent of the newborns had a good neonatal outcome, whereas the other 22% were admitted to a neonatal intensive care unit for an average period of 17 days. The most frequent neonatal morbidity was respiratory. One newborn died. Despite the need for several attempts of assisted reproductive technology, pregnancy complications, neonatal morbidity and mortality, the use of these techniques allowed for most couples to overcome their infertility problem.